Dwelling on the Future Architecture of the Seaside, Middle England and the Metropolis - d'Avoine, Pierre (Design Research in Architecture, 2020)
Dwelling on the Future focuses on the design of dwellings and their varied environments, and questions how an architect responds to the challenge of providing humane places in which to live for a growing, multifarious population in an increasingly divided world. The issue is never just housing. People - individuals, groups and societies - can and do have different goals and aspirations. Is it possible to imagine and implement a world in which a level of comfort and stability is available for even the poorest members of societies? Pierre d'Avoine covers a wide range of examples, including proposals for luxury housing and designs for low-cost dwellings, which all address the needs and desires of their potential inhabitants. He explores an inclusive approach to the design of settlements - and not just in cities - that recognises difference, an approach that demands a fresh political vision to resolve humanity's increasing inequality, for the benefit of all. D'Avoine asks if we can respond with optimism to the Kabakovs' mordantly titled installation 'Not Everyone Will Be Taken Into the Future (2001)'. While this was perhaps a statement of fact in Russia and elsewhere in the Soviet Union during the Cold War, it is implicit, and ever more so, in the West today. Praise for Dwelling on the Future 'Beautifully judged line drawings, physical models and critical texts ...supplemented here by interviews that he has conducted with the full range of project partners. These illuminate the rich, diverse and often idiosyncratic contexts within which housing in the UK is produced and prove that good housing is not merely a socio-technical process. The resulting proposals suggest the triumph of possibility over regulatory limitation ...As the Welsh Government's laudable Innovative Housing Programme progresses, Dwelling on the Future illustrates the value of different ways of thinking and acting.' Touchstone: The journal for architecture in Wales 'The merits of the images [in paperback] out perform the on-screen version.'Construction Expert, Russia 'In the modern world, with its growing speed and increasingly widespread clip-based thinking, it is rare to find an architect's book about architecture in which text prevails over images. ...Dwelling on the Future is also unusual in that it is based not on a text by the architect about his projects, but on a series of interviews with those who were involved in them. ...The book should be of interest to anyone who is curious about the origins of architectural ideas, projects and the process of their implementation.' Gleb A. Sobolev ''The ultimate problem for the profession is that of setting out the possibilities and choices in building and environment.' - Architect and educator Leslie Martin (1967) In this valuable book[the] projects, individually and in sum, are 'possibilities and choices' for housing in the 21st century.' Buildings & Cities